Multimodality in glottodidactics: Some considerations on the glottodidactic analysis of internet specialist texts - Szerszeń, Paweł (Wydział Neofilologii UAM w Poznaniu i Wydział Lingwistyki Stosowanej UW, 2014)
The main purpose of this article is to reflect on the question of multimodality in a glottodidactic context, by way of an analysis of internet specialist texts (IST). Here, I take multimodality to mean all the communicative modalities undertaken by man, as distinguished from multimediality, which is defined as an interaction of various technical media in delivering a message. This two dimensions (multimodality and multimediality) are strictly related and interdependent. First, I present a few terminological remarks about expressions that are of key importance for understanding the subject-matter at hand: multimodality, multimediality, electronic hypertext and internet specialist texts. Next, I describe selected changes to the glottodidactic system caused by the Internet, with particular emphasis on changes in the way in which internet texts are formulated. Referring to F. Grucza’s anthropocentric theory of human languages, I draw attention to the structure of internet hypertexts and internet specialist texts and the possibility of a glottodidactic description thereof. Regarding the latter, I present the criteria governing a glottodidactic analysis of internet specialist texts, after which I enumerate and discuss the determinants for applying internet texts to the teaching of specialist languages. Finally, I indicate new areas of research into the glottodidactic potential of IST, taking into account the multimodal dimension.
Keywords: multimodality; glottodidactic; internet specialist texts; multimediality